2013
DOI: 10.1073/pnas.1300127110
|View full text |Cite
|
Sign up to set email alerts
|

Convergent gene loss following gene and genome duplications creates single-copy families in flowering plants

Abstract: The importance of gene gain through duplication has long been appreciated. In contrast, the importance of gene loss has only recently attracted attention. Indeed, studies in organisms ranging from plants to worms and humans suggest that duplication of some genes might be better tolerated than that of others. Here we have undertaken a large-scale study to investigate the existence of duplication-resistant genes in the sequenced genomes of 20 flowering plants. We demonstrate that there is a large set of genes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
378
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(419 citation statements)
references
References 59 publications
37
378
3
1
Order By: Relevance
“…Species with or without WGD that branch within the same group, such as the deuterostomes Homo sapiens and Ciona intestinalis or the fungi Allomyces macrogynus and the chytrids, show similar TFome profiles in terms of the proportions of each TF class, suggesting that this tendency is independent of TF type. This is consistent with the finding that TFs are one of the gene classes that are most resilient to loss after WGD (28,29). As for the total number of TFs, the proportion of TFs in a genome (as a fraction of the total number of proteins) also varies considerably.…”
Section: Resultssupporting
confidence: 88%
“…Species with or without WGD that branch within the same group, such as the deuterostomes Homo sapiens and Ciona intestinalis or the fungi Allomyces macrogynus and the chytrids, show similar TFome profiles in terms of the proportions of each TF class, suggesting that this tendency is independent of TF type. This is consistent with the finding that TFs are one of the gene classes that are most resilient to loss after WGD (28,29). As for the total number of TFs, the proportion of TFs in a genome (as a fraction of the total number of proteins) also varies considerably.…”
Section: Resultssupporting
confidence: 88%
“…We identified putative dosage-sensitive singletons as genes present in single copy in all of human, chimpanzee, macaque, mouse, rat, dog, cow, opossum and chicken. We examined CNVs neighbouring these 1,151 singletons and found that they were unlikely to display CNVs (21.9%, 252/1,151; P ÂŒ 3.0  10 À 14 , w 2 test), which is consistent with the hypothesis that these are dosage-sensitive genes 37 . We observed a strong positive correlation between P CNV of non-singletons and distance to singletons for non-singletons on a 0.0-0.5 Mb scale (Supplementary Fig.…”
Section: Less Frequent Cnvs Of Genes Neighbouring Ohnologssupporting
confidence: 68%
“…Furthermore, non-ohnologs within ORRs were likely to be singletons in all genomes analysed (purported dosage-sensitive singletons as described above; Table 1; P ÂŒ 1.0  10 -8 , w 2 test). The dosage-sensitive singletons within ORRs are likely to be genes that returned to single-copy status from ohnologs after WGD 37 . These results indicate that non-ohnologs within ORRs may also be dosage-sensitive genes.…”
Section: Less Frequent Cnvs Of Genes Neighbouring Ohnologsmentioning
confidence: 99%
“…Duplicated genes are generated by several DNA-and RNA-based mechanisms (Innan and Kondrashov, 2010;Sakai et al, 2011). Whole-genome DNA-based duplication (WGD) by polyploidization has occurred in the evolutionary history of all land plants and many animals (Dehal and Boore, 2005;De Smet et al, 2013). Since WGD amplifies the entire genome, it seems to be a solution toward major evolutionary and/or ecological challenges (Comai, 2005;Fawcett et al, 2009).…”
Section: Introductionmentioning
confidence: 99%